PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF BAWANG DAYAK (ELEUTHERINE SP.) AND HATI TANAH (ANGIOPTERIS SP.) AND THEIR COMBINATION AGAINST PROPIONIBACTERIUM ACNES - NOVARYATIIN, SUSI (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to investigate the preliminary phytochemical screening and antibacterial activity of Bawang Dayak (Eleutherine sp.) and Hati Tanah (Angiopteris sp.) and their combination against Propionibacterium acnes. Methods: The extracts were used for phytochemical screening. Antibacterial activity was performed using disc diffusion technique, with two variations of the concentration of 5% and 10% for each extracts, and combination of both extracts with three combinations: (1) 5%: 5%, (2) 5%: 10%, and (3) 10%: 5%. Results: Both extracts contained tannins, saponins, and steroids. The antibacterial activity against P. acnes showed that the inhibition zones of Bawang Dayak ethanol extract were 6.1±1.5 mm (5%) and 8.7±1.3 mm (10%). On the other hand, the inhibition zones of Hati Tanah ethanol extract were 4.0±1.6 mm (5%) and 9.2±2.5 mm (10%). The inhibition zones produced in combinations 1, 2, and 3 were 5.8±0.3 mm, 10.8±2.0 mm, and 15.5±2.8 mm, respectively. Conclusion: In this study showed the presence of tannins, saponins, and steroids that might be responsible for antibacterial activity in both extract. The best antibacterial activity was produced by combining the two extracts (combination 3).